Double-segregated multiwalled carbon nanotube/silicone composites with large electrical to thermal conductivity ratios via in-situ silicone emulsion polymerization. (September 2020) - Kim, Dongouk; Lee, Sang-Eui; Sohn, Yoonchul
Polymer composites with a high electrical conductivity ( σ ) to thermal conductivity ( k ) ratio have been intensively investigated in recent years. While highly conductive materials, such as metallic fillers or conducting polymers, were used to enhance σ, microstructural engineering was used to decrease k by forming porous structures, such as aerogels or 3D networks. These structures, however, were mechanically vulnerable and could only have limited applications. In this study, multiwalled carbon nanotube /silicone composites with a high σ/k ratio were developed by forming a double-segregated multiwalled carbon nanotube network in the porous body of the composites. The unique microstructure of the composites was created by a novel fabrication process: layer-by-layer deposition with in-situ polymerization of silicone emulsion particles dispersed in a water solvent. This novel process yielded very thick films, >200 µm, with high σ/k values, ∼2 × 10 4 (S/m)/(W/m·K). These high σ/k composites can be used for various applications, such as resistive heating elements, thermoelectric materials, and wearable thermotherapy.